Occurrence of ferret enteric coronavirus in Brazil: (preliminary report) - Gregori, Fabio (2010)
Ferret enteric coronavirus (FECV) is associated to the epizootic catarrhal enteritis (ECE) in ferrets (Mustela putorius furo). In this study, we report the occurrence of this agent in four diarrheic stool samples of domestic ferrets, analyzed by negative staining transmission electron microscopy and a specific RT-PCR assay targeting the nucleocapsid (N) gene. These findings are the first report of FECV in Brazil and address the importance of this virus on the etiology of enteric disorders in ferrets.